Maintained hypotheses and questions in search of answers - Marc Gaudry; Émile Quinet (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2012)
We propose a series of kick-off points related to the economic appraisal of large urban infrastructure projects, taking some account of the specifics raised by the Grand Paris Express (GPE) regional automatic metro. The points, in the form of Maintained Hypotheses or Questions in Need of Answers, are crystallised around three orientations: demand model properties; overall effects on urbanisation; extensions of traditional appraisal. The conclusion contains a list of hard problems dodged and issues ignored in the discussion.
Keywords: 330